SURFACE DEFORMATIONS NEAR THE BAIKAL–AMUR RAILWAY FROM DIFFERENTIAL SAR INTERFEROMETRY DATA - M. A. Lebedeva; V. A. Sankov; A. I. Zakharov; L. N. Zakharova (Геодинамика и тектонофизика, 2016)
This paper presents SAR interferometric data obtained in the study of surface deformations of different origin within the Upper Angara-Muya interbasin link of the northeastern segment of the Baikal rift system, Russia. Differential SAR interferometry using images with small perpendicular baselines was applied in this geodynamical study. The potential of using ENVISAT/ASAR and ALOS/PALSAR data is discussed. New geodynamical data on recent strain patterns were obtained. The endogenous linear-localized and areal deformations were revealed in the influence zone of the active Muyakan fault. The origin of these deformations is discussed. The landslide that negatively affects the Baikal-Amur railway facilities is also studied. The use of SAR data for detailed study and monitoring of the landslide is discussed. It is confirmed that natural hazard in the study area is growing due to the ongoing landsliding.